1998
DOI: 10.1002/jor.1100160505
|View full text |Cite
|
Sign up to set email alerts
|

Cultured human ankle and knee cartilage differ in susceptibility to damage mediated by fibronectin fragments

Abstract: According to numerous cadaveric, radiographic, and clinical studies, ankle and knee joints differ in susceptibility to osteoarthritis. To test for biochemical differences in susceptibility to damage, a chondrocytic chondrolysis system has been utilized. In this system, fibronectin fragments are added to cultured cartilage explants, resulting in enhanced release of catabolic cytokines, induction of matrix metalloproteinases, temporary suppression of proteoglycan synthesis, and consequently, severe loss of carti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 12 publications
2
41
0
Order By: Relevance
“…This difference may be one of the main reasons for increased cartilage degeneration and the high rate of primary OA in the knee [9,41]. Although the ankle cartilage is thinner compared with knee or hip cartilage (ankle, 1.0-1.62 mm; knee, 1.69-2.55 mm; hip, 1.35-2.0 mm) [35], the ankle cartilage shows a higher compressive stiffness and proteoglycan density [41], lower matrix degradation [1], and less response to catabolic stimulations (as interleukin 1, fibronectin fragments) [5,15]. This fact of relative higher cartilage resistance might protect the ankle from degenerative changes leading to primary OA.…”
Section: Discussionmentioning
confidence: 99%
“…This difference may be one of the main reasons for increased cartilage degeneration and the high rate of primary OA in the knee [9,41]. Although the ankle cartilage is thinner compared with knee or hip cartilage (ankle, 1.0-1.62 mm; knee, 1.69-2.55 mm; hip, 1.35-2.0 mm) [35], the ankle cartilage shows a higher compressive stiffness and proteoglycan density [41], lower matrix degradation [1], and less response to catabolic stimulations (as interleukin 1, fibronectin fragments) [5,15]. This fact of relative higher cartilage resistance might protect the ankle from degenerative changes leading to primary OA.…”
Section: Discussionmentioning
confidence: 99%
“…Via diffusion, these cytokines may stimulate chondrocytes to produce more inflammatory mediators such as prostaglandin E2, nitric oxide, or matrix metalloproteinases (MMPs) that inhibit proteoglycan and collagen synthesis and promote extracellular matrix degradation. 18 For example, previous studies have shown a significantly lower catabolic response of ankle cartilage to IL-1, 17,18 or fibronectin fragments, 19 as compared to knee cartilage. This difference in cellular response may, in part reflect the lower partition coefficient of ankle cartilage, which would effectively reduce the interstitial concentration of such soluble mediators for an equivalent concentration in the external bathing solution or synovial fluid.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted, however, that the molecule used in this experiment was a linear 70-kDa dextran, whereas IL-1 and fibronectin fragments are 17.5-and 29-kDa molecules, respectively. 19,45 It remains to be determined whether the difference in partition would still be observed using smaller, globular molecules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ankle chondrocytes are less responsive than those of knee cartilages to catabolic mediators Section 2.2 64-such as interleukin-1 or fibronectin fragments, and have lower gene expression of certain matrix metalloproteinases (e.g., MMP-8) [41,42,97,119]. Since talar cartilage is thinner, the superficial zone comprises a higher proportion of the full thickness and thus may provide a protective layer more resistant to damage.…”
Section: Introductionmentioning
confidence: 99%